Collective Biography of Female Anarchists Participating in the Free Women and Libertarian Movements. (December 2015) - Duque, Elena
The Free Women movement was a women's organization that actively participated in the Spanish Social Revolution (1936-1939). It was the first organization of working women created to fight for their rights independent of any political party or trade union and was established by young women participating in the libertarian movement. These women and other members of the National Workers Confederation and the Libertarian Youth promoted cultural training for the working class. They organized spaces for workers to meet, read, and discuss relevant books together. Through the biographical method, with a communicative approach, the authors collected the life narratives of some women who participated in this movement. Using women's stories and the existing historical documents, the authors created a collective biography focusing on those spaces in which libertarian women discussed book readings. Such spaces are closely related to the current practice of dialogic gatherings and were a key element in improving education.